2022
DOI: 10.5334/aogh.3704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Urinary Schistosomiasis among Primary School Pupils in the Jidawa and Zobiya Communities of Jigawa State, Nigeria

Abstract: Background: Urogenital schistosomiasis (UgS) is a parasitic disease caused by Schistosoma haematobium and can lead to chronic ill-health. Nigeria is endemic for schistosomiasis, but epidemiology of UgS has not been studied in most states. This study was conceived with the aim to contribute towards an accurate national picture of UgS in Nigeria. The prevalence of UgS and the associated risk factors were for the first time investigated among primary school pupils in Jidawa and Zobiya communities of the Dutse Loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The very high prevalence of S. haematobium infection in urine samples that had haematuria is similar to the 98 -100% prevalence reported in urine samples with haematuria by Balogun et al (2022). The implication of this is that in endemic regions, it is fair to conclude that the presence of blood in urine of children serves as strong prognosis of urogenital schistosomiasis (Balogun et al, 2022). A high rate of macrohaematuria among children in this study is an indication of high infection intensity which portends risk of bladder carcinogenesis at old age (Umar et al, 2016).…”
Section: Prevalence Rate Of Schistosoma Haematobium Infection Accordi...supporting
confidence: 79%
See 2 more Smart Citations
“…The very high prevalence of S. haematobium infection in urine samples that had haematuria is similar to the 98 -100% prevalence reported in urine samples with haematuria by Balogun et al (2022). The implication of this is that in endemic regions, it is fair to conclude that the presence of blood in urine of children serves as strong prognosis of urogenital schistosomiasis (Balogun et al, 2022). A high rate of macrohaematuria among children in this study is an indication of high infection intensity which portends risk of bladder carcinogenesis at old age (Umar et al, 2016).…”
Section: Prevalence Rate Of Schistosoma Haematobium Infection Accordi...supporting
confidence: 79%
“…Similarly, a high infection prevalence of 70% has previously been reported among communities in Minjibir Local Government Area, Kano State (Umar et al, 2016), with a relatively lower prevalence rate of 37% reported in community around Wasai Dam, in Minjibir of Kano State (Enabulele et al, 2021). Balogun et al (2022) reported similar high prevalence of 65.7% and 69.0% in the Jidawa and Zobiya communities of Jigawa State.…”
Section: Prevalence Rate Of Schistosoma Haematobium Infection Accordi...mentioning
confidence: 73%
See 1 more Smart Citation
“…10 Identifying areas where these infections occur, and studying their co-infection, risk factors and implication on anaemia and nutritional status will increase the efficiency and proper implementation of control or elimination programmes. 11 Based on previous studies, urinary schistosomiasis is prevalent in Jigawa State 12 , and work has been done on its co-infection with malaria and its effect on anaemia and nutritional status. In this study, we sought to determine whether there is a significant co-infection of urogenital schistosomiasis and malaria and its risk of anaemia and malnutrition amongst schoolchildren in the areas around Dutse in Jigawa State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, more than 250 million people in the tropics and subtropics required treatment in 2021 . Morbidity associated with the disease arises from immunopathological reactions to parasite eggs that accumulate in different tissues depending on the Schistosoma species. , This can result in chronic pain and malaise that may interfere with academic performance in school and the ability to perform manual labor, which, among other more life-threatening morbidities, limits the economic productivity of the subsistence communities affected. , Treatment and control of disease rely on the use of a single drug, praziquantel, which acts on a calcium-permeable ion channel. , The drug has a number of pharmacological and pharmaceutical drawbacks, including poor efficacy against developing schistosomes, and with the concern of resistance, there is a need to identify novel antischistosomal drugs. …”
mentioning
confidence: 99%